Corynebacterium aquaticum septicaemia in a neutropenic patient. Issue 10 (October 1995) - Moore, C; Norton, R
Abstract : Corynebacteria are a well recognised cause of sepsis in the immunocompromised patient. Corynebacterium aquaticum, however, is rarely seen in the clinical setting, being an environmental organism associated with fresh water. A septicaemic episode caused by this organism in a 74 year old neutropenic woman with an indwelling central venous catheter is reported. It is postulated that the source of the organism was untreated stored rainwater which she used for showering.